(untitled) (Research, Society and Development, 2021)
Objective: To identify risk factors and causes for prematurity in newborns (NBs) in a hospital institution. Method: Documentary, descriptive study with a quantitative approach, carried out in a hospital in the interior of the state of Rio Grande do Sul. The population consisted of 58 premature NBs, who had complete records at the institution. The search for premature NBs was carried out in the birth book of the institution’s Obstetric Center and data were collected from the clinical records of the NBs and their mothers. For data tabulation and organization, we used the Microsoft Excel 2013 software and statistical analysis, the Statistical Package for Social Science (SPSS), version 21 software. Results: The results obtained in the research on possible risk factors related to prematurity in NBs were: maternal age, obstetric, genetic and physiological history, lifestyle and number of prenatal consultations. And the causes evidenced were: female genital tract, placental changes and hypertensive syndromes. Also, data on the two types of preterm births: spontaneous and elective are present in the study. Conclusion: it is essential to have knowledge of health professionals about the risk factors and the causes that allow the pregnant woman to have a premature birth during her prenatal monitoring through consultations during the pregnancy period. Thus, the results found in this research become relevant in academic training and technical-scientific development for professional practice, which can provide subsidies to optimize the planning of health policies aimed at this specific audience.